Advancing health care quality and safety through action learning. Issue 2 (2nd May 2017) - Mathews, Simon; Golden, Sherita; Demski, Renee; Pronovost, Peter; Ishii, Lisa
Abstract : Purpose: The purpose of this study is to demonstrate how action learning can be practically applied to quality and safety challenges at a large academic medical health system and become fundamentally integrated with an institution's broader approach to quality and safety. Design/methodology/approach: The authors describe how the fundamental principles of action learning have been applied to advancing quality and safety in health care at a large academic medical institution. The authors provide an academic contextualization of action learning in health care and then transition to how this concept can be practically applied to quality and safety by providing detailing examples at the unit, cross-functional and executive levels. Findings: The authors describe three unique approaches to applying action learning in the comprehensive unit-based safety program, clinical communities and the quality management infrastructure. These examples, individually, provide discrete ways to integrate action learning in the advancement of quality and safety. However, more importantly when combined, they represent how action learning can form the basis of a learning health system around quality and safety. Originality/value: This study represents the broadest description of action learning applied to the quality and safety literature in health care and provides detailed examples of its use in a real-world context.